Que hay en el cielo, querido dragon? = What's in the sky, dear dragon? - Hillert, Margaret; Schimmell, David; Fernandez, Queta; Hillert, Margaret; Hillert, Margaret (Chicago, Illinois : Norwood House Press, 2014)
"A boy and his pet dragon look at both the day and night skies. They learn about the sun, moon, animals, and airplanes that move through the sky. This title includes reading activities"--
Parallel text in Spanish and English.
Keywords: Sky -- Juvenile fiction; Dragons -- Juvenile fiction; Cielo -- Novela juvenil; Dragones -- Novela juvenil; Sky -- Fiction; Dragons -- Fiction; Spanish language materials -- Bilingual; Dragons; Sky; Readers (Publications); Fiction; Juvenile works; Readers (Publications)